Propeller diffusion weighted imaging for diagnosis of cholesteatoma in comparison with surgical and histopathological results: Emphasis on false positivity and false negativity - SEMİZ OYSU, ASLIHAN; OYSU, ÇAĞATAY (My University, 2023)
PurposeTo investigate the role of non-echo planar diffusion weighted imaging (DWI) using \"periodically rotated overlapping parallel lines with enhanced reconstruction\" (PROPELLER) sequence for the diagnosis of cholesteatoma compared to surgical and histopathological results in an attempt to determine the factors causing false negative and false positive diagnoses.MethodsPatients who had PROPELLER DWI before ear surgery were retrospectively reviewed. The presence of a lesion with diffusion restriction on PROPELLER DWI was accepted as positive for cholesteatoma, and the results were compared to the intraoperative and histopathological findings.ResultsA total of 112 ears in 109 patients were reviewed. On PROPELLER DWI, a lesion with diffusion restriction was found in 101 (90.2%) ears, while in 11 (9.8%) of the patients, no diffusion restriction was found. Surgery and histopathological analysis revealed a cholesteatoma in 100 (89.3%) ears, while in 12 (10.7%) ears, no cholesteatoma was found surgically. There were 96 (85.7%) true positives, 7 (6.2%) true negatives, 5 (4.5%) false positives and 4 (3.6%) false negatives. The accuracy, sensitivity, specificity, positive predictive and negative predictive values of non-echo planar DWI were calculated to be 91.96%, 96%, 58.33%, 95.05%, and 63.64%, respectively.ConclusionNon-echo planar DWI using PROPELLER sequence has high accuracy, sensitivity and positive predictive value and can be used for the detection of cholesteatoma. The external auditory canal, postoperative ears and small lesions should be evaluated with caution to avoid false results.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; KULAK BURUN BOĞAZ; Klinik Tıp; Klinik Tıp (MED); OTORHINOLARYNGOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Konuşma ve İşitme; Speech and Hearing; Otorhinolaryngology; Cholesteatoma; Diffusion weighted magnetic resonance imaging; Temporal bone; Diagnostic imaging; Otologic surgical procedures; PITFALLS; MRI